2018
DOI: 10.1155/2018/3056562
|View full text |Cite
|
Sign up to set email alerts
|

The Volume-Outcome Relationship in Retroperitoneal Soft Tissue Sarcoma: Evidence of Improved Short- and Long-Term Outcomes at High-Volume Institutions

Abstract: Background We sought to study the association between RPS case volume and outcomes. Although a relationship has been demonstrated between case volume and patient outcomes in some cancers, such a relationship has not been established for retroperitoneal sarcomas (RPSs). Study Design The National Cancer Database (NCDB) was queried for patients undergoing treatment for primary RPS diagnosed between 2004 and 2013. Mean annual patient volume for RPS resection was calculated for all hospitals and divided into low vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 16 publications
4
41
0
2
Order By: Relevance
“…In response to this call, several investigators have demonstrated a strong relationship between hospital volume and favorable RPS operative outcomes. [11][12][13][14] Further, 2 recent French analyses assessing quality of sarcoma care delivered in a regionalized system uncovered improved outcomes in patients attending designated "reference" centers for sarcoma, which use at minimum, multidisciplinary tumor boards and 2 pathologist reviews of histologic specimens. 15,16 Despite the call for regionalization of RPS surgery in the United States and its supportive evidence, this trend lags significantly behind other regionalized complex surgical cancers, such as pancreatic.…”
mentioning
confidence: 99%
“…In response to this call, several investigators have demonstrated a strong relationship between hospital volume and favorable RPS operative outcomes. [11][12][13][14] Further, 2 recent French analyses assessing quality of sarcoma care delivered in a regionalized system uncovered improved outcomes in patients attending designated "reference" centers for sarcoma, which use at minimum, multidisciplinary tumor boards and 2 pathologist reviews of histologic specimens. 15,16 Despite the call for regionalization of RPS surgery in the United States and its supportive evidence, this trend lags significantly behind other regionalized complex surgical cancers, such as pancreatic.…”
mentioning
confidence: 99%
“…However, retroperitoneal sarcomas (RPS) are among the largest tumors in the human body and in addition to their large size, their proximity to critical organs and major vessels makes surgery very challenging. As expected, multiple studies to date have demonstrated that outcomes for RPS patients are clearly better when they are managed by specialists vs nonspecialists 3–5 …”
mentioning
confidence: 58%
“…In conclusion, just as sommeliers have an important, very specific role in the dining experience for a restaurant patron, sarcoma specialists are critical for the patient with this rare and challenging cancer. Institutional thresholds for high case volume (eg, for RPS, >10 per year) have been proposed and deserve further study 3,4 ; but in reality, many sarcoma specialists as defined above would far exceed these numbers. Referral to a sarcoma specialist has the additional benefit of centralizing research efforts and facilitating enrollment into therapeutic clinical trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also possible that the lack of change reflects a lack of referrals to specialized centers. The etiology of the static rate of MVR warrants attention in future studies as this may be a target for increasing both MVR rates and referrals to specialized sarcoma centers with the goal of improving both postoperative morbidity and mortality as well as oncologic outcomes …”
Section: Discussionmentioning
confidence: 99%